The Optical Properties of Pyrochlore Oxides R₂Mo₂O₇_δ (R: Sm, Gd, and Ho), The Heavy-Fermion UNi₂Al₃, and The Organic Conductor (TMTSF)₂ClO₄ - Cao, Ning (My University, 1995)
The temperature dependence of the reflectance of the spin-glass materials R₂Mo₂O₇_δ (R: Sm, Gd, and Ho) has been measured for frequencies from 40 to 40,000 cmˉ¹. The real part of the AC conductivity of Sm₂Mo₂O₇_δ, derived from Krarners-Kronig analysis, indicates a Drude-like behavior as the temperature is lowered. Between 150 and 40 K the scattering rate shows a sharp drop which is attributed to the scattering of conduction electrons by short-range ordered moments of the Mo ions. Below the spin-glass transition temperature Tf(≅40 K) the scattering rate saturates due to the freezing out of the moments. Gd₂Mo₂O₇_δ behaves like a poor metal at room temperature, but at low temperatures shows a linear increase in the conductivity for frequencies up to 400 cmˉ¹ suggesting a localized hoping conductivity. The localization remains in the spin-glass state for T
The optical properties of the new heavy-fermion superconductor UNi₂Al₃ have been investigated at temperatures between 10 and 300 K using reflectance spectroscopy. A characteristic energy scale (ωc≅90 cmˉ¹), with almost the same value as the characteristic temperature T₀ derived from measurements of the DC resistivity and susceptibility, is obtained from the optical conductivity. At high temperatures (T>T₀), this scale represents the energy gap between the ground and excited level that results from the crystal-field splitting of the 5f² (J=4) level of the tetravalent uranium ion. In the low-temperature coherent region (T
The polarized optical reflectance of the quasi-one-dimensional organic conductor (TMTSF)₂ClO₄ has been measured along the chain axis from the far-infrared (~8 meV) to the visible (~1 eV) at temperatures between 10 and 300 K. The real part of the optical conductivity shows that a gap (2Δ≅21 meV) develops in the conductivity at low temperatures that may be related to the long-range ordering of SDW found in the NMR measurement for T < Tc³ᴰ≅25 K. Precursors of the SDW gap (pseudogap) that may result from the one-dimensional SDW fluctuations are visible as high as 100 K and are also indicated by both the temperature dependent integrated conductivity spectral weight between 2Δ and 1000 cmˉ¹ and intensity of the phase phonons. Our results suggest that the very high DC conductivity of this material at low temperatures is carried by a narrow mode at zero frequency. This narrow mode has been supported by both the fitting of the reflectance data below 60 K to a Drude term plus the other terms and the large negative values in ε₁(ω) at low frequencies. The spectral weight associated with this narrow mode decreases sharply with increasing temperature which is similar to the temperature dependence of the spectral weight of the induced phonons found in far-infrared. This indicates that both the narrow zero-frequency mode and the induced phonons have the same collective-excitation origin in this quasi-one-dimensional material.
Keywords: Physics; Physics